Saberes, relações e práticas da alimentação em uma escola da rede pública de Boquim/SE - Castro, Edjane dos Santos (2022)
Through food, the numerous animal and plant species obtain the nutrients necessary for development. But, with regard to the human being, food goes beyond this scope of survival, being immersed in a network of social, cultural and identity relationships with subjective consequences. In this context, the production and transmission of knowledge about food are also presented, with knowledge, beliefs and customs being passed on from generation to generation. However, as science advanced, there was a kind of institutionalization of food, which began to be influenced by the medical field and a biologicist discourse that occupies a prominent position in societies. This is present in the school environment through a curriculum committed to capital. At the same time, the school is a social space that favors the practice of commensality, which is the act of eating together, the interaction at the time of eating. In public schools, food is the object of the Programa Nacional de Alimentação Escolar (PNAE) and, thus, is immersed in political aspects that determine what is eaten, how to eat and knowledge about it. Faced with these questions, the general objective of this dissertation is: To understand the knowledge and practices related to food produced and maintained by students from a public school in the municipality of Boquim/SE and their relationship with institutionalized food knowledge. A qualitative and descriptive methodology was adopted, with the development of a bibliographic and field research. As a theoretical contribution, studies in the area of Food Anthropology and notions of the relationship with knowledge, by Bernard Charlot, were sought. The observation of school lunches, the application of questionnaires and the carrying out of individual interviews with students from the 8th year of Elementary School to the 3rd year of High School generated data that were analyzed in the light of Content Analysis, by Laurence Bardin. The results show that students conceive food as synonymous with health and nutrition, do not see themselves as holders of important and valid knowledge about the food phenomenon and have difficulty expressing experiences and situations with eating and the food that marked them. The biomedical perspective is used as a filter in the remembrance of events and relationships with food and food, helping to limit the effects of food intake on the body. The conclusion is that the lunch should appear as a transversal component of learning, considering its potential for teaching the different aspects of human existence and society worked in the various areas of knowledge. Thus, it will be possible to develop a more reflective, contextualized teaching that makes sense for everyone.